(untitled) (Iter, 2022)
As Kwiatkowska (2001:15) points out throughout history, man has always had a particular relationship, more or less close, with nature; and that relationship manifests itself both in their way of thinking or speaking, and in their behavior. Just as the paintings, the poems, the varied literary, scientific, historical or philosophical texts, reveal the thought and feeling of a determined human group with respect to their natural environment, so the epigraphic documents express, in another way, their specific relationship with nature. The present work intends to analyze in some of these documents the way in which the ancient Greeks were linked to their natural environment. Along with the linguistic considerations that will certainly arise from the analysis of the inscriptions, we believe that this other point of view, which springs up in general from questions typical of daily life, that they reflect, can be extremely significant.